Fintech P2P Lending dan Pengaruhnya Terhadap Pertumbuhan Ekonomi Indonesia - Yasir Maulana; Herma Wiharno (Indonesian Journal of Strategic Management, 2022)
Previous research has shown that fintech contributes to GDP and reduces numbers and poverty. However, this does not cover the fact that P2P lending still has the potential to develop and have a positive impact on Indonesia's economic growth. This study examines the effect of P2P lending fintech on Indonesia's economic growth, using secondary data on Indonesia's economic growth from Bank Indonesia and P2P lending fintech data from the Financial Services Authority (OJK). Simple regression statistical analysis, t-test, and coefficient of determination show that peer to peer (P2P) lending has a positive and significant impact on Indonesia's economic growth. A total of 74.60 percent of the P2P lending variables explain the variables of Indonesia's economic growth. These results indicate that the growth of P2P lending is driving Indonesia's economic growth. This positive influence can be explained based on the relationship between P2P credit and other variables that affect the economy such as labor absorption variables through MSMEs, poverty rates, Gini ratio, GDP, growth of other economic sectors, household consumption levels, and inflation rates. This relationship is explained descriptively based on the results of previous studies.